A novel solid PEO/LLTO-nanowires polymer composite electrolyte for solid-state lithium-ion battery. (1st December 2018) - Zhu, Lin; Zhu, Penghui; Fang, Qunxiang; Jing, Maoxiang; Shen, Xiangqian; Yang, Lezhi
Abstract: In this study, fast ionic conductor Li0.33 La0.557 TiO3 (LLTO) nanowires with high ionic conductivity were prepared through electrospinning and subsequent high temperature calcination. It was filled in the poly(ethylene oxide) (PEO) matrix as a filler and the novel solid PEO/LiTFSI/LLTO-nanowires polymer composite electrolytes were prepared via solution casting method with low cost. The results showed that the addition of LLTO nanowires could effectively improve the ionic conductivity, electrochemical stability window, transference number, and compatibility with lithium metal of polymer composite electrolytes. The maximum ionic conductivities of composite electrolytes filled with 5 wt% LLTO nanowires at room temperature and 60 °C were 5.53 × 10 −5 S cm −1 and 3.63 × 10 −4 S cm −1, respectively. Its electrochemical stability window was up to 4.75 V. The LiFePO4 /Li solid-state lithium-ion battery assembled with the novel polymer composite electrolytes had good cycling stability. At current rate of 0.5 C, the discharge specific capacity remained about 123 mAh g −1 after 100 cycles at 60 °C. Highlights: LLTO nanowires with high ionic conductivity were prepared by electrospinning and subsequent high temperature calcination. LLTO nanowires were filled into PEO based polymer electrolyte to improve the ionic conductivity of solid electrolytes. The solid state lithium ion battery delivered good electrochemical performance.